Zoning of the reaction of the tissues of the implantation area after prosthetic repair in abdominal hernias in experiment - E. E. Lukoyanychev; S. G. Izmailov; D. A. Evsyukov; V. O. Nikolskij; A. A. Mironov; A. V. Panyushkin (Исследования и практика в медицине, 2022)
Purpose of the study. Development of criteria for evaluating the reaction of tissues in the implantation area after prosthetic repair of the hernia ring in an experiment using new digital image processing technologies.Materials and methods. The experiment was carried out on 13 Wistar rats of different sexes. Under anesthesia, a 4 × 2 cm mesh prosthesis was implanted in the layer similar to the onlay epiaponeurotic. The preparation and staining of each preparation was carried out in two versions: with hematoxylin-eosin and according to Mallory on different glasses. The seasons for performing experiments are winter, summer. Microphotography was performed on a medical transmitted light microvisor Microvisor μVizo‑103 (AD LOMO, Russia) with a 3.2 Mpx matrix (full frame size 1024 × 882 px, infoband width 88 px) with Planachromat and Stigachromat lenses with a digital scale × 1 (i.e. no digital zoom). Microphoto processing was performed using the ImageJ 1.53k program (version for public use). The criterion for including a microphoto in the calculation of indicators was the presence of an ingrown implant fiber in the preparation or a cavity surrounding the implant.Results. The zone adjacent to the implant, with a width of about 50 µm ("the zone of changes in adjacent tissues") significantly differs from the "zone of changes in distant tissues" by a more pronounced inflammatory reaction due to a larger absolute number of lymphocytes (р = 0.019 and fibroblasts (р = 0.017), giant cells of foreign bodies (р < 0.001), larger vascular area (р < 0.001) and extravasations (р = 0.002). The study of the "zone of changes in adjacent tissues" is of key importance in assessing the local response of the body to implantation. The key zones of the implantation area are identified: "the cavity surrounding the implant", "the zone of changes in adjacent tissues", "the zone of changes in distant tissues". The calculation of indicators within these zones allows you to get more detailed results when comparing study groups in the experiment.Conclusion. An effective method for assessing the reaction of tissues in the implantation area after prosthetic hernia repair in an experiment using new digital imaging technologies that can be used using a conventional optical microscope and standard staining methods is proposed.